2012
DOI: 10.1016/j.devcel.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

FoxA Family Members Are Crucial Regulators of the Hypertrophic Chondrocyte Differentiation Program

Abstract: During endochondral ossification small immature chondrocytes enlarge to form hypertrophic chondrocytes, which express collagen X. In this work, we demonstrate that FoxA factors are induced during chondrogenesis, bind to conserved binding sites in the collagen X enhancer, and can promote the expression of a collagen X-luciferase reporter in both chondrocytes and fibroblasts. In addition, we demonstrate by both gain and loss of function analyses that FoxA factors play a crucial role driving the expression of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 50 publications
(59 reference statements)
5
72
1
Order By: Relevance
“…This is consistent with our finding because Runx2 is a known downstream target for BMP signaling (28). Also, Smads and Runx2 have been reported to interact in the transcription of collagen type X (18,29,30). Interestingly, we identified three conventional Smad-binding sites in the 250-bp basic COL10A1 promoter (Fig.…”
Section: Identification Of An Ihh-responsive Element In the Col10a1 Psupporting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with our finding because Runx2 is a known downstream target for BMP signaling (28). Also, Smads and Runx2 have been reported to interact in the transcription of collagen type X (18,29,30). Interestingly, we identified three conventional Smad-binding sites in the 250-bp basic COL10A1 promoter (Fig.…”
Section: Identification Of An Ihh-responsive Element In the Col10a1 Psupporting
confidence: 81%
“…3, A and C). In addition to Runx2/3, previous studies have shown that chondrocyte hypertrophy is also regulated by Mef2c/d and Foxa2/3 (16,18,23). However, our data show that Ihh did not induce Mef2c, Foxa2, or Foxa3 mRNA expression (Fig.…”
Section: Identification Of An Ihh-responsive Element In the Col10a1 Pcontrasting
confidence: 54%
See 2 more Smart Citations
“…SOX9 has been proposed to both prevent cells from prematurely entering the prehypertrophic stage and to promote the subsequent hypertrophy (Dy et al 2012). The transcription factors FoxA2 and FoxA3 are necessary for chondrocyte hypertrophy (Ionescu et al 2012). SHOX2, a homeodomain-containing transcription factor, is necessary for RUNX2/RUNX3 expression and hypertrophy within the stylopod (see Box 1) (Cobb et al 2006;Yu et al 2007).…”
Section: Nuclear Factors Regulating Growth Plate Developmentmentioning
confidence: 99%